Pengaruh Motivasi Eksternal dan Motivasi Internal terhadap Kinerja Karyawan pada TK Budi Mulia Dua Pandeansari - Efa Nur Cholis; Djoko Wijono (Jurnal Maksipreneur, 2014)
This study aimed to examine the influence of external and internal motivation on employee performance in TK Budi Mulia Dua Pandeansari. The sample in this study were all employees in TK Budi Mulia Dua Pandeansari. Samples were collected using a total sampling. There were 50 respondents who have met the necessary conditions. The analytical method used is multiple regression analysis. The results showed that the external and internal motivation effect on employee performance. The results of multiple regression analysis showed that the variables of external and internal motivation have coefficient of 0.703 and 0.450. The results showed that the external and internal motivation has given Adjusted R Square of 0.575 or 57.5%.